2003
DOI: 10.1038/sj.bjc.6601114
|View full text |Cite
|
Sign up to set email alerts
|

CD1a-positive infiltrating-dendritic cell density and 5-year survival from human breast cancer

Abstract: Infiltrating CD1aþ dendritic cells (DCs) have been associated with increased survival in a number of human cancers. This study investigated DC infiltration within breast cancers and the association with survival. Classical established prognostic factors, of tumour size, lymph node status, histological grade, lympho-vascular invasion, the KI-67 (MIB-1) fraction and the Nottingham Prognostic Index (NPI) were also compared. A total of 48 breast cancer patients were followed from the time of surgery and CD1a densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
44
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 54 publications
6
44
2
2
Order By: Relevance
“…Moreover, we suppose that CD1a expression may have an antitumoral role in BM mucosa, and also, as postulated, in neoplastic diseases arising at other anatomic sites (Coventry and Morton, 2003a;Coventry and Heinzel, 2004;Poindexter et al, 2004). As a future objective, epithelial CD1a þ cells interaction with DCs or T cells remains to be further investigated.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Moreover, we suppose that CD1a expression may have an antitumoral role in BM mucosa, and also, as postulated, in neoplastic diseases arising at other anatomic sites (Coventry and Morton, 2003a;Coventry and Heinzel, 2004;Poindexter et al, 2004). As a future objective, epithelial CD1a þ cells interaction with DCs or T cells remains to be further investigated.…”
Section: Discussionmentioning
confidence: 79%
“…The antitumoral role of CD1a was recently proposed (Coventry and Morton, 2003a;Coventry and Heinzel, 2004;La Rocca et al, 2004). We also recently described that CD1a could be expressed in metaplastic epithelium of Barrett's oesophagus, both gastric and intestinal types, while normal gastric and colonic mucosa were negative to this marker (Cappello et al, 2003).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Central to pathways for activating tumor antigen-specific T cell and antibody responses is the uptake, processing, and presentation of the tumor antigen by dendritic cells (DC), professional antigen presenting cells [1,2]. The importance of endogenous DC has been highlighted by better clinical outcomes for patients with various tumor types when DC are found to be infiltrating the tumor [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…I read with interest the article of Coventry and Morton (2003) that investigated DC infiltration within breast cancers and the association with survival. Interestingly, they found that more patients were alive at the 5-year time point in the group with higher CD1a DC density than the lower CD1a DC group, but this failed to reach statistical significance at the P ¼ 0.05 level.…”
Section: Sirmentioning
confidence: 99%